CD34+ cell of origin for immunoglobulin heavy chain variable region unmutated, but not mutated, chronic lymphocytic leukemia. Issue 7 (7th June 2022) - Perkins, Brandy; Showel, Margaret; Schoch, Laura; Imus, Philip H.; Karantanos, Theodoros; Yonescu, Raluca; Morsberger, Laura; Ghiaur, Gabriel; Gladstone, Douglas E.; Jones, Richard J.
Abstract: The clinical course of chronic lymphocytic leukemia (CLL) is highly variable. Immunoglobulin heavy chain variable region (IgHV) mutation status is among the most important prognostic factors, with unmutated IgHV associated with inferior outcomes. CLL presumably arises from mature B cells. However, we hypothesized that IgHV unmutated CLL could arise early in B cell differentiation. We prospectively studied 29 patients with mutated and 88 with unmutated IgHV CLL for the presence of CD34 + CD19 + cells harboring CLL chromosomal abnormalities. CD34 + CD19 + cells were never detected in mutated CLL. In contrast, a small but distinct population of CD34 + CD19 + cells harboring the CLL chromosomal abnormality was present in 86/88 patients with unmutated IgHV across all cytogenetic subtypes. Moreover, the CD34 + CD19 + cells generated a 3.8 ± 0.7 fold CLL cell expansion over 3–4 weeks in cultures containing IL-3 and IL-2. Unmutated IgHV CLL appears to arise in CD34 + B cells, which perhaps contributes to its poorer prognosis.